THE EFFECT OF INFRASTRUCTURE AND WORK ENVIRONMENT ON PRIVATE MADRASAH TSANAWIYAH TEACHERS' PERFORMANCE IN CENTRAL JAKARTA - GEOVANI, Muhammad Alvin (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2024)
Teachers' performance can be influenced by limited educational facilities and infrastructure, such as small classrooms, insufficient learning equipment, and inadequate facilities. The lack of access to technology, like computers and multimedia devices, can hinder the use of diverse teaching methods and innovations. Additionally, an unsafe work environment and poor building conditions can negatively impact teachers' well-being and performance. This study aims to examine: 1) The impact of infrastructure on the performance of private Tsanawiyah Madrasah teachers in Central Jakarta, 2) The effect of the work environment on teacher performance, and 3) The relationship between infrastructure and the work environment. The study uses a quantitative approach. The population consists of 184 teachers from Tsanawiyah Madrasah in Central Jakarta. Using the Slovin formula, the sample size was determined to be 124 teachers. The findings show that: 1) Infrastructure facilities (X1) account for 41% of the impact on teacher performance (X3), with the remaining 59% influenced by factors not explored in this study. 2) The work environment (X2) accounts for 45.4% of the impact on teacher performance (X3), while 54.6% is influenced by other factors. 3) Infrastructure facilities (X1) account for 67.9% of the impact on the work environment (X2), with the remaining 32.1% influenced by other factors not examined in this study.